Primary follicular lymphoma of colon: A case series and review of literature - Mohammed, Abdul (Clin Case Rep, 2021)
Follicular lymphoma of the colon is rare, accounting for 1% to 2% of cases in the gastrointestinal tract. Despite the absence of randomized clinical trials, NCCN stage III and IV colonic follicular lymphomas are routinely treated with chemotherapy with good clinical response. We present 2 cases of advanced stage follicular lymphoma of colon that were effectively treated with bendamustine‐based chemotherapy regimens.